The interaction of legal and social norm enforcement - Kube, Sebastian; Traxler, Christian (Munich, 2010)
"Although legal sanctions are often non-deterrent, we frequently observe compliance with ‘mild laws’. A possible explanation is that the incentives to comply are shaped not only by legal, but also by social sanctions. This paper employs a novel experimental approach to study the link between legal and social norm enforcement. We analyze whether the two institutions are complements or substitutes. Our results show that legal sanctions partially crowd out social norm enforcement. The welfare effect from mild laws is positive, however, as a higher level of compliance is achieved at lower enforcement costs."